Si/Ag composite with bimodal micro-nano porous structure as a high-performance anode for Li-ion batteries1. Issue 12 (28th March 2015) - Hao, Qin; Zhao, Dianyun; Duan, Huimei; Zhou, Qiuxia; Xu, Caixia
<x xml:space="preserve">Abstract</x> A bimodal porous Si/Ag composite is easily fabricated by etching an SiAgAl alloy in HCl solution, and performs excellently for lithium storage.